2019
DOI: 10.23925/2176-901x.2019v22i3p301-317
|View full text |Cite
|
Sign up to set email alerts
|

Oficina “MemorIdade”: impactos na cognição e queixa de memória em idosos de um Centro de Convivência

Abstract: Objetivou-se avaliar os efeitos promovidos por uma oficina de memória na cognição e queixa subjetiva de memória, em idosos de um Centro de Convivência. Dez idosos participaram da oficina, que constou de nove encontros semanais que abordaram diversos aspectos, com foco na memória episódica, operacional, e na linguagem. Foi observada melhora significativa nos domínios cognitivos memória e linguagem após a oficina, bem como aumento das queixas subjetivas de memória.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 21 publications
0
0
0
Order By: Relevance
“…International studies such as the cross-sectional one carried out with middle-aged caregivers in France 10 and the population-based study conducted in Germany with aged caregivers 6 identified that informal caregivers' cognition is influenced by the care they offer, especially females 6 . In this way, the high stress levels resulting from the daily care burden can put the caregivers' cognitive health at risk and make memory failure complaints emerge 11 .…”
Section: Introductionmentioning
confidence: 99%
“…International studies such as the cross-sectional one carried out with middle-aged caregivers in France 10 and the population-based study conducted in Germany with aged caregivers 6 identified that informal caregivers' cognition is influenced by the care they offer, especially females 6 . In this way, the high stress levels resulting from the daily care burden can put the caregivers' cognitive health at risk and make memory failure complaints emerge 11 .…”
Section: Introductionmentioning
confidence: 99%